Improvement of Power System Loading Margin with Reducing Network Investment Cost Using SVC - Srikumar, K. (Asian Journal of Electrical Sciences, 2019)
Under emergency conditions to reduce the harms from environmental deterioration, one of the recently focused developments in the power industry is to make the existing transmission networks sufficiently utilize their capability in power transfer. From the detailed analysis and many studies, voltage instability was found to be the main factor responsible for several blackout events. As an index to indicate the level of static voltage stability of a transmission system, the Loading Margin (LM) or Voltage Stability Margin (VSM), represents the maximum power that can be transferred between generators and loads before voltage collapse point achieved is generally measured in system planning. In this paper, under each contingency with high Risk Index (RI) value, the Modal Analysis (MA) technique is used to determine which buses need Static VAR Compensator (SVC) installation, and with maximum LM and minimum SVC installation cost composed into the multi-objective function. The optimal LM enhancement problem is formulated as a multi-objective optimization problem (MOP) and solved by using the fitness sharing multi-objective particle swarm optimization (MOPSO) algorithm for a Pareto front set. The proposed method may be tested on the IEEE 24-bus reliability test system (RTS) and IEEE 14-bus system.